DAMPAK KEMACETAN LALU LINTAS TERHADAP PRODUKTIVITAS KERJA DI SURABAYA - Oktaviani Permatasari (STIE Mahardhika, 2020)
The effect of road traffic congestion on the development of workers in Surabaya, Indonesia, has been examined. The people studied were employed by staff from various private and public companies in the city of Surabaya. The data was obtained through standard questionnaires from 63 sample companies from various Surabaya companies. Knowledge is asked about how traffic jams affect efficiency, results, development, happiness, innovation, quality of work, and how this affects goals set in the workplace. Staff performance measures the final results that impact traffic congestion variables. Themes such as productivity, effectiveness, employee career growth, satisfaction, innovation, and quality of work have determined performance construction. The data was analyzed using descriptive statistics and multiple regressions.